Large Fibroepithelial Polyp of Vulva - Mahesha H. Navada; Poornima Ramachandra B. Bhat; Sujaya V. Rao; Nagarathna G. (Hindawi Limited, 2011)
A rare case of a large fibroepithelial polyp (FEP) of the vulva is described. The polypoidal growth was 10 cm in its largest diameter, having a long pedicle with features of inflammation secondary to infection, and was found arising from the left labia majora. The patient did not manifest any signs of recurrence following excision. A large and infected FEP of the vulva is a rare occurrence and hence reported.